2017
DOI: 10.1021/acs.bioconjchem.7b00174
|View full text |Cite
|
Sign up to set email alerts
|

Dual Plug-and-Display Synthetic Assembly Using Orthogonal Reactive Proteins for Twin Antigen Immunization

Abstract: Engineering modular platforms to control biomolecular architecture can advance both the understanding and the manipulation of biological systems. Icosahedral particles uniformly displaying single antigens stimulate potent immune activation and have been successful in various licensed vaccines. However, it remains challenging to display multiple antigens on a single particle and to induce broader immunity protective across strains or even against distinct diseases. Here, we design a dually addressable synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
128
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 50 publications
(108 reference statements)
1
128
0
Order By: Relevance
“…We also demonstrated that those conjugates exhibited a range of different functions (Bae et al, ; Choi et al, ; Moon et al, ). The ST/SC protein ligation system has been applied for displaying various antigenic proteins and targeting ligands on VLPs and their effective immune response inductions and cell‐specific gene delivery were successfully demonstrated (Brune et al, , ; Bruun, Andersson, Draper, & Howarth, ; Janitzek et al, ; Kasa, Raneni, Chamoun‐Emanuelli, Wright, & Chen, ; Ke et al, ; Leneghan et al, ; Singh et al, ; Thrane et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that those conjugates exhibited a range of different functions (Bae et al, ; Choi et al, ; Moon et al, ). The ST/SC protein ligation system has been applied for displaying various antigenic proteins and targeting ligands on VLPs and their effective immune response inductions and cell‐specific gene delivery were successfully demonstrated (Brune et al, , ; Bruun, Andersson, Draper, & Howarth, ; Janitzek et al, ; Kasa, Raneni, Chamoun‐Emanuelli, Wright, & Chen, ; Ke et al, ; Leneghan et al, ; Singh et al, ; Thrane et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Howarth group has developed orthogonally reactive split proteins such as SpyCatcher/SpyTag—by splitting a domain from the fibronectin‐binding protein of Streptococcus pyrogenes —and SnoopCatcher/SnoopTag—by splitting an adhesin from Streptococcus pneumonia . More recently, Brune et al . genetically fused the sequences for SpyCatcher and SnoopCatcher to different termini of the multimerized coiled‐coil IMX313 scaffold and expressed the final construct in E. coli (Figure ).…”
Section: Multivalency In Immune Cell Modulationmentioning
confidence: 99%
“…Due to strong and rapid reactions between the tags and the complementary Catchers, the authors were able to covalently link the antigens to the IMX platform, which was demonstrated to be stable even under non‐ideal conditions. In addition, during animal studies, the multivalent construct resulted in an antibody response 10‐fold higher than the one using soluble monovalent antigens …”
Section: Multivalency In Immune Cell Modulationmentioning
confidence: 99%
See 2 more Smart Citations